Polymer, photosensitive resin composition, resin film, and electronic device
Patent Information
- Application Number
- JP2021548837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-26
- Filing Date
- 2020-09-15
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-09-15
AI Technical Summary
【0013】 本発明によれば、耐熱性および耐溶剤性に優れるとともに、低誘電性の樹脂膜を製造するために好適に用いることができるポリマーが提供される。
Smart Images

Figure 0007639688000001 
Figure 0007639688000002 
Figure 0007639688000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer, a photosensitive resin composition, a resin film, and an electronic device. More specifically, the present invention relates to a polymer, a photosensitive resin composition containing the polymer, a resin film made of a cured product of the photosensitive resin composition, and an electronic device including the resin film. [Background technology]
[0002] In the field of negative photosensitive resin compositions, various techniques have been developed to improve the accuracy of resist patterns associated with finer patterns. For example, a technique described in Patent Document 1 is one such technique. According to the same document, a radiation-sensitive resin composition containing a polymer [A] and an acid generator [B] is described. It is also described that the polymer [A] has a structural unit (I) and a structural unit (II), and thus has excellent LWR (Line Width Roughness) performance and defect suppression properties, which indicate a small line width jitter (paragraph 0012 of Patent Document 1). Here, it is described that the structural unit (I) is a structural unit derived from N-(t-butyloxycarbonylmethyl)maleimide, N-(1-methyl-1-cyclopentyloxycarbonylmethyl)maleimide, or N-(2-ethyl-2-adamantyloxycarbonylmethyl)maleimide. It is also described that the structural unit (II) is a structural unit derived from 2-norbornene. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-184458 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have studied the durability of negative-type photosensitive resin compositions. As a result, it has been found that the radiation-sensitive resin composition described in Patent Document 1 has room for further improvement in terms of durability and low dielectric properties. The present invention provides a photosensitive resin composition having an excellent balance between durability and low dielectric properties, and a polymer for use in such a photosensitive resin composition.
[0005] The present inventors have found that by using a polymer having a structural unit with a specific structure, a cured product of a photosensitive resin composition containing the polymer has improved heat resistance, improved solvent resistance and a low dielectric constant, and have completed the present invention. [Means for solving the problem]
[0006] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a polymer having a specific fluorine-containing organic group.
[0007] According to the present invention, there is provided a polymer comprising structural units represented by the following formulas (1) and (2a):
[0008] [ka] (In formula (1), R 1 , R 2 , R 3 and R 4 at least one of the groups is a perfluoroalkyl group having 1 to 30 carbon atoms, and the rest are hydrogen atoms; n is 0, 1 or 2; In formula (2a), R 5 teeth, An organic group having 1 to 30 carbon atoms and a (meth)acryloyl group. .).
[0009] Further, according to the present invention, A polymer comprising structural units represented by the following formulas (1) and (2a): A cross-linking agent; A photosensitive resin composition is provided that includes a photosensitizer.
[0010] [ka] (In formula (1), R 1 , R 2 , R 3 and R 4 at least one of the groups is a perfluoroalkyl group having 1 to 30 carbon atoms, and the rest are hydrogen atoms; n is 0, 1 or 2; In formula (2a), R 5 teeth, An organic group having 1 to 30 carbon atoms and a (meth)acryloyl group. .).
[0011] According to the present invention, there is also provided a resin film comprising a cured film of the above photosensitive resin composition.
[0012] Furthermore, according to the present invention, there is provided an electronic device comprising the above-mentioned resin film. Effect of the Invention
[0013] According to the present invention, there is provided a polymer which has excellent heat resistance and solvent resistance and can be suitably used for producing a low dielectric resin film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described.
[0015] (Polymer P) The polymer of this embodiment (hereinafter referred to as "polymer P") contains structural units represented by the following formulas (1) and (2a).
[0016] [ka] Here, in formula (1), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom or an organic group having 1 to 30 carbon atoms, and n represents 0, 1, or 2; In formula (2a), R 5 is an organic group having 1 to 30 carbon atoms, R 1 , R 2 , R 3 , R 4 and R 5 At least one of them is a fluorine-containing organic group having 1 to 30 carbon atoms.
[0017] Since the polymer P contains the structural units described above, the cured product thereof has excellent heat resistance and solvent resistance as well as low dielectric properties, and is therefore suitable for use as a material for producing resin films for electronic devices.
[0018] Polymer P has a structural unit derived from a norbornene type monomer represented by formula (1) and a structural unit derived from maleic anhydride represented by formula (2a).
[0019] [ka]
[0020] In formula (1), n is 0, 1 or 2, and is preferably 0. R 1 , R 2 , R 3 and R 4 each independently represents hydrogen or an organic group having 1 to 30 carbon atoms. In formula (2a), R 5 is an organic group having 1 to 30 carbon atoms. R 1 , R 2 , R 3 , R 4 and R 5 At least one of them is a fluorine-containing organic group having 1 to 30 carbon atoms.
[0021] The proportion of the structural units represented by formula (1) in all structural units of the polymer P is preferably 35 mol % or more and 70 mol % or less, more preferably 40 mol % or more and 60 mol % or less.
[0022] R in formula (1) and formula (2a) 1 , R 2 , R3 and R 4 , and R 5 Examples of the organic group having 1 to 30 carbon atoms that can constitute any one of the above include an alkyl group, an alkenyl group, an alkynyl group, an alkylidene group, an aryl group, an aralkyl group, an alkaryl group, a cycloalkyl group, and a heterocyclic group. Examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, and decyl groups. Alkenyl groups include, for example, allyl, pentenyl, and vinyl groups. Alkynyl groups include ethynyl groups. Alkylidene groups include, for example, methylidene and ethylidene groups. Aryl groups include, for example, phenyl, naphthyl, and anthracenyl groups. Aralkyl groups include, for example, benzyl and phenethyl groups. Examples of the alkaryl group include tolyl and xylyl groups. Examples of the cycloalkyl group include adamantyl, cyclopentyl, cyclohexyl, and cyclooctyl groups. Examples of the heterocyclic group include an epoxy group and an oxetanyl group.
[0023] The organic group having 1 to 30 carbon atoms may contain at least one atom selected from O, N, S, P and Si in its structure.
[0024] In one embodiment, the organic group having 1 to 30 carbon atoms is preferably an organic group having 1 to 15 carbon atoms, and more preferably an organic group having 1 to 10 carbon atoms. Furthermore, the organic group having 1 to 30 carbon atoms is preferably an alkyl group having 1 to 30 carbon atoms, and more preferably an alkyl group having 1 to 15 carbon atoms, and even more preferably an alkyl group having 1 to 10 carbon atoms.
[0025] In the polymer P, R 1 , R 2 , R 3 , R 4、 and R 5 At least one of them is a fluorine-containing organic group having 1 to 30 carbon atoms. Examples of the fluorine-containing organic group having 1 to 30 carbon atoms include a fluoroalkyl group having 1 to 30 carbon atoms and a fluoroalkyl group having 1 to 30 carbon atoms and having an etheric oxygen atom. The fluoroalkyl group having 1 to 30 carbon atoms refers to an organic group in which one or more hydrogen atoms in an alkyl group are substituted with a fluorine atom. Such a fluoroalkyl group includes a fluorinated alkyl group and a perfluoroalkyl group.
[0026] In one embodiment, R 1 , R 2 , R 3 and R 4 Preferably, any one of R is a fluorine-containing organic group having 1 to 30 carbon atoms, and the remaining is a hydrogen atom. 1 , R 2 , R 3 and R 4 More preferably, any one of R is a fluoroalkyl group having 1 to 30 carbon atoms, and the remaining is a hydrogen atom. 1 , R 2 , R 3 and R 4 Any one of R is a perfluoroalkyl group having 1 to 30 carbon atoms, and the rest are hydrogen atoms. 1 , R 2 , R 3 and R 4 When any one of them is a fluorine-containing organic group having 1 to 30 carbon atoms and the remainder is a hydrogen atom, the film-forming properties of the photosensitive resin composition containing this polymer P can be improved and the obtained cured film can have low dielectric properties.
[0027] In one embodiment, R 5 is preferably a fluoroalkyl group having 1 to 30 carbon atoms or a fluoroalkyl group having 1 to 30 carbon atoms and an etheric oxygen atom.
[0028] In one embodiment, R 1 , R 2 , R 3 and R 4 The organic group constituting the polymer P is preferably an organic group having no acidic functional group. By not having an acidic organic group, the acid value of the polymer P can be easily controlled.
[0029] The polymer P of this embodiment may further contain at least one of the structural units represented by formulas (B2) to (B6).
[0030] [ka]
[0031] [ka]
[0032] [ka]
[0033] [ka]
[0034] [ka]
[0035] In the formula (B2), R 6 and R 7 are each independently an organic group having 1 to 30 carbon atoms. In formula (B6), R 8 is an organic group having 1 to 30 carbon atoms. The organic group having 1 to 30 carbon atoms has the same definition as above. R 5 , R 6 , R 7It is preferable that any one of the above groups has a carbon-carbon double bond that can be crosslinked by a photoradical polymerization initiator. Examples of the group include a vinyl group, a vinylidene group, an allyl group, an acryloyl group, and a methacryloyl group.
[0036] Among these, it is preferable to contain a structural unit derived from maleimide represented by formula (B5) or formula (B6) because the heat resistance of the resulting cured film is improved. 6 ~R 8 It is preferable that none of the organic groups constituting the polymer P have an acidic functional group such as a carboxyl group, which makes it easier to control the acid value of the polymer P.
[0037] The polymer P of this embodiment can be prepared by addition polymerization of a norbornene type monomer (monomer A) represented by formula (3) and maleic anhydride (monomer B) represented by formula (4). When the polymer P of this embodiment further contains structural units represented by formula (B5) and / or formula (B6), the norbornene type monomer (monomer A) can be addition polymerized with maleic anhydride and maleimide and / or maleimide derivative (monomer B) represented by formula (5) to prepare the desired polymer.
[0038] [ka]
[0039] [ka]
[0040] [ka] In formula (3), n is 0, 1 or 2; R 1 , R 2 , R 3 and R 4 each independently represents hydrogen or an organic group having 1 to 30 carbon atoms. In formula (5), R 8is the same as the definition above.
[0041] Norbornene-type monomers that can be used include, for example, the following norbornenes:
[0042] [ka]
[0043] [ka]
[0044] [ka]
[0045] [ka]
[0046] [ka]
[0047] [ka]
[0048] [ka]
[0049] Examples of the maleimide derivative represented by the above formula (5) include N-methylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, N-(4-aminophenyl)maleimide, N-benzylmaleimide, N-tert-butylmaleimide, N-ethylmaleimide, N-(2-hydroxyethyl)maleimide, N-methoxycarbonylmaleimide, 3-maleimidepropionic acid, 4-maleimidebutyric acid, and 6-maleimidehexanoic acid. Among these, it is preferable to use N-cyclohexylmaleimide. This can improve the heat resistance and chemical resistance of the cured product of the polymer P.
[0050] The polymer P can be synthesized by an addition polymerization reaction between a monomer A and a monomer B. It should be noted that there is no limitation to using one type or two or more types of monomers as the monomer A and the monomer B. Although there is no limitation on the method of addition polymerization, in this embodiment, the copolymer is synthesized by radical polymerization using a radical polymerization initiator. By performing addition polymerization using a radical polymerization initiator, a copolymer having a structural unit derived from monomer A and a structural unit derived from monomer B, and having a terminal derived from the radical polymerization initiator, can be synthesized.
[0051] The molar ratio of monomer A to monomer B in the copolymer is preferably 1:0.5 to 1:2. The above 1:0.5 to 1:2 includes 1:0.5 and 1:2. Among these, from the viewpoint of improving controllability of molecular structure, the molar ratio is preferably 1:1.
[0052] Monomer A, monomer B, and a radical polymerization initiator are dissolved in a solvent, and then heated for a predetermined time to allow addition polymerization to proceed. The heating temperature is, for example, 50° C. or higher and 80° C. or lower, and the heating time is 3 hours or higher and 20 hours or lower.
[0053] In the addition polymerization, additives such as a chain transfer agent may be used. It is preferable to add a chain transfer agent to control the terminal structure of the copolymer and introduce a functional group that reacts with a crosslinking agent to the copolymer terminal.
[0054] The radical polymerization initiator is not limited as long as it introduces a functional group that reacts with the crosslinking agent to X, which is one of the copolymer terminals, and an azo compound or a peroxide can be used. Among these, it is preferable to use an azo compound.
[0055] Specific examples of the azo compound include radical polymerization initiators having a carboxyl group such as 4,4'-azobis(4-cyanovaleric acid) and 2,2'-azobis[N-(2-carboxyethyl)-2-methyl]; radical polymerization initiators having an amino group such as 2,2'-azobis(2-methylpropionamidine) and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]; and radical polymerization initiators having a hydroxyl group such as 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide]. Among these, it is preferable to use a radical polymerization initiator having a carboxyl group, and it is even more preferable to use 4,4'-azobis(4-cyanovaleric acid). This can improve the heat resistance and chemical resistance of the resulting polymer P.
[0056] The amount (number of moles) of the radical polymerization initiator added is preferably 1% or more and 10% or less of the total number of moles of monomer A and monomer B. By appropriately setting the amount of the radical polymerization initiator within the above range and also appropriately setting the reaction temperature and reaction time, the weight average molecular weight (Mw) of the resulting copolymer can be adjusted.
[0057] The copolymer obtained by the addition polymerization reaction of monomer A and monomer B (referred to as "polymer precursor" or "polymer before ring-opening") becomes polymer P by the ring-opening process. In the ring-opening process, among the structural units derived from maleic anhydride in the polymer precursor obtained as described above, some repeating units are in a ring-closed state, while the remaining repeating units are ring-opened. This makes it possible to adjust the amount of carboxyl groups in the copolymer. That is, it becomes possible to control the acid value of the copolymer to be produced. And, by controlling the acid value, it is possible to adjust the alkali solubility of the photosensitive resin composition containing polymer P.
[0058] In this embodiment, for example, 50% or more of the repeating units derived from maleic anhydride in the polymer precursor are not ring-opened, and the cyclic structures (anhydride rings) of the remaining repeating units are ring-opened. That is, the ring-opening rate of the copolymer is, for example, less than 50%. In particular, it is preferable to ring-open 10% or more and 30% or less of the repeating units of the cyclic structure derived from maleic anhydride in the copolymer.
[0059] Here, the ring-opening ratio of the repeating unit derived from maleic anhydride can be measured as follows. The IR absorption intensity (Abs1) of (C=O) in the acid anhydride structure of the polymer (polymer precursor) before ring-opening is measured, and the ring-opening rate is calculated from the IR absorption intensity (Abs2) of (C=O) in the acid anhydride structure after ring-opening using the following formula. Ring opening rate (%)=(((Abs1)-(Abs2)) / (Abs1))×100 Acetonitrile is used as the internal standard substance.
[0060] The polymer precursor is treated with either (i) a metal alkoxide as a base, (ii) an alcohol and an alkali metal hydroxide as a base, or (iii) an alcohol and an organic base such as a tertiary amine to form a polymer P in which the maleic anhydride structural unit is ring-opened. Specifically, in the polymerization step, the above-mentioned reagent (i) or (ii) is added to the reaction solution in which the monomers A and B are polymerized, and an organic solvent such as methyl ethyl ketone (MEK) is further added, and the mixture is stirred at 40°C to 50°C for 1 hour to 5 hours to obtain a reaction solution L1. In the reaction solution L1, some of the anhydride rings of the repeating units derived from maleic anhydride in the copolymer are ring-opened, and some of the ends formed by the ring-opening are esterified. The remaining ends are not esterified, but become metal salt structures.
[0061] In this embodiment, the molar number of the metal alkoxide or alkali metal hydroxide is preferably 50% or less of the molar number of the maleic anhydride used in the polymerization step. In particular, the molar number of the metal alkoxide or alkali metal hydroxide is preferably 40% or less, 10% or more, and more preferably 30% or less of the molar number of the maleic anhydride used in the polymerization step. In this way, the amount of the metal alkoxide or alkali metal hydroxide can be reduced, and the alkali metal concentration in the finally obtained polymer P can be reduced. By reducing the alkali metal concentration in the polymer P, migration of metal ions in a device using a resin composition using this polymer P can be suppressed.
[0062] The metal alkoxides mentioned above include M(OR 5 ) (M is a monovalent metal, R 5 is an organic group having 1 to 30 carbon atoms.) is preferable. Examples of the metal M include alkali metals, and among them, sodium is preferable from the viewpoint of ease of handling. R 5 As an example of the R 5 The same can be mentioned. Two or more different metal alkoxides may be used, however, from the viewpoint of production stability, it is preferable to use one type of metal alkoxide.
[0063] On the other hand, as described above, the structure derived from maleic anhydride, which is a polymer precursor, may be ring-opened (ii) in the presence of an alcohol and an alkali metal hydroxide as a base. As the alkali metal hydroxide, sodium hydroxide is preferred from the viewpoint of ease of handling. As for alcohol, monohydric alcohol (R 5 OH) is preferred. 5 The above-mentioned can be used for R. 5 has preferably 1 to 30 carbon atoms.
[0064] The monohydric alcohol (R 5OH) include allyl alcohol, methallyl alcohol, 3-buten-1-ol, 3-methyl-3-buten-1-ol, 4-penten-1-ol, 5-hexen-1-ol, 6-hepten-1-ol, 7-octen-1-ol, 8-nonen-1-ol, 9-decen-1-ol, 10-undecen-1-ol, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 1,4-cyclohexanedimethanol monoacrylate, and 1,4-cyclohexanedimethanol monomethacrylate, 1H,1H-trifluoroethenol, 1H,1H-pentafluoropropanol, 6-(perfluoroethyl)hexanol, 1H,1H-heptafluorobutanol, and Examples of perfluoropropanol include, but are not limited to, 2-(perfluorobutyl)ethanol, 3-perfluorobutyl)propanol, 6-(perfluorobutyl)hexanol, 2-perfluoropropoxy-2,2,3,3-tetrafluoropropanol, 2-(perfluorohexyl)ethanol, 3-(perfluorohexyl)propanol, 6-(perfluorohexyl)hexanol, 1H,1H-2,5-di(trifluoromethyl)3,6-dioxaundecafluorononanol, 6-(perfluoro-1-methylethyl)hexanol, 1H,1H,3H-tetrafluoropropanol, 1H,1H,5H-octafluoropentanol, 1H,1H,7H-dodecafluoroheptanol, 2H-hexafluoro-2-propanol, 1H,1H,3H-hexafluorobutanol, and 2,2-bis(trifluoromethyl)propanol. These alcohols may be used alone or in combination of two or more.
[0065] The repeating unit derived from maleic anhydride opened in this ring-opening step has a structure represented by the following formula (5a), which has a salt moiety of a carboxyl group.
[0066] [ka] (In formula (5a), R 5 is an organic group having 1 to 30 carbon atoms.
[0067] In addition, when the copolymer is ring-opened with (i) a metal alkoxide as a base, or (ii) an alcohol and an alkali metal hydroxide as a base, structures shown in the following general formula (B2) and the following formula (5b) may be formed, although only slightly. In the following general formula (B2), R 6 , R 7 is the above R 5 It may be the same as:
[0068] [ka] (In formula (B2), R 6 , and R 7 are each independently an organic group having 1 to 30 carbon atoms.
[0069] [ka]
[0070] After the ring-opening reaction, a monomer having an epoxy group and a double bond group can be further reacted to obtain a polymer P having a crosslinkable double bond-containing group. In this embodiment, it is preferable to use glycidyl acrylate, glycidyl methacrylate, or 3,4-epoxycyclohexylmethyl methacrylate as the monomer having an epoxy group and a double bond group, in view of availability. It is also possible to introduce a fluorine functional group by reacting a monomer having an epoxy group and a fluorine functional group in a similar manner. For example, 3-perfluorobutyl-1,2-epoxypropane, 3-perfluorohexyl-1,2-epoxypropane, 3-perfluorooctyl-1,2-epoxypropane, etc. can be used. By providing the polymer P with a group having a double bond, the crosslinkability by a photoradical polymerization initiator can be improved, and as a result, the sensitivity of the polymer P can be improved.
[0071] Next, an acidic aqueous solution of hydrochloric acid, formic acid, or the like is added to the reaction solution L1 to acidify the copolymer, thereby ionizing the copolymer. + ) to proton (H + ) The structural unit represented by the above formula (6) becomes the structural units represented by the following formulas (2a) and (B4) by proton substitution, respectively.
[0072] [ka] (In formula (2a), R 5 is an organic group having 1 to 30 carbon atoms.
[0073] [ka]
[0074] In this ring-opening step (S3), it is preferable not to open 50% or more of the repeating units derived from maleic anhydride in the polymer precursor. As described above, in the polymer P, a metal such as Na is bonded to one end formed by ring-opening of the maleic anhydride ring, but by not opening 50% or more of the repeating units, the amount of metal contained in the product polymer P can be reduced. This makes it possible to reduce the amount of alkali metal in the polymer P finally obtained in this embodiment, and to make the photosensitive resin composition containing this polymer P exhibit desired properties.
[0075] After the ring-opening step, the solution containing the obtained polymer P may be washed with a mixture of water and an organic solvent (e.g., methyl ethyl ketone) to remove residual metal components. It is preferable to carry out the washing step so that the alkali metal concentration in the polymer P is 10 ppm or less, preferably 5 ppm or less.
[0076] The weight average molecular weight (Mw) of the polymer P of this embodiment is preferably in the range of 1000 to 20000, more preferably 1500 to 15000, and even more preferably 2000 to 10000 from the viewpoint of forming an appropriate crosslinked structure. The number average molecular weight (Mn) of the polymer P of this embodiment is preferably 500 to 10000, and more preferably 1000 to 8000 from the viewpoint of forming an appropriate crosslinked structure. Furthermore, from the viewpoint of making the physical properties of each molecular chain of the polymer P uniform and improving the shape of the resin film obtained by curing, the molecular weight distribution (Mw / Mn) of the polymer P is preferably 1.0 to 2.5, and more preferably 1.2 to 2.0. The molecular weight of the polymer P can be controlled by adjusting the type of the above-mentioned monomer used in the preparation of the polymer P, the amount of the monomer, the preparation conditions, and the like.
[0077] The double bond equivalent of the polymer P of this embodiment is preferably 500 g / mol or more and 2500 g / mol or less, more preferably 500 g / mol or more and 2000 g / mol or less. Since the double bond equivalent is within the above range, the polymer P is suitably used in a photosensitive resin composition that is subjected to exposure and development treatment.
[0078] The fluorine content of the polymer P of this embodiment is preferably 25 wt% or more and 45 wt% or less, more preferably 30 wt% or more and 40 wt% or less. When the fluorine content is in the above range, the cured product of the polymer P has excellent heat resistance and solvent resistance. The fluorine content of the polymer P can be controlled by adjusting the type and the amount of the monomer used in the preparation of the polymer P.
[0079] The polymer P of this embodiment has excellent alkali solubility, and therefore has excellent processability in exposure and development treatment using an alkaline aqueous solution as a developer. The alkaline dissolution rate of the polymer P can be, for example, 10 Å / sec to 2500 Å / sec, more preferably 50 Å / sec to 2000 Å / sec. Here, the alkaline dissolution rate is calculated by applying a propylene glycol monomethyl ether acetate solution (solid content 35% by mass) of the polymer P to a silicon wafer by spin coating and soft baking at 100°C for 120 seconds to obtain a polymer film, which is then immersed in a 2.38% aqueous tetramethylammonium hydroxide solution at 23°C, and measuring the time it takes for the polymer film to be visually erased.
[0080] The polymer P of the present embodiment has a refractive index of, for example, 1.38 to 1.48, more preferably 1.40 to 1.46. The polymer P having a refractive index within the above range has excellent processability by exposure and development, and the cured product thereof has desired properties as a permanent film for electronic devices.
[0081] (Photosensitive resin composition) The polymer P of this embodiment is used in a photosensitive resin composition for forming a resin film of an electronic device. The photosensitive resin composition of the present embodiment is The polymer P, A cross-linking agent; and a photosensitizer.
[0082] The photosensitive resin composition of the present embodiment contains the above-mentioned polymer P, and thus the cured product has excellent heat resistance and solvent resistance as well as low dielectric properties. Therefore, the photosensitive resin composition of the present embodiment can be suitably used as a material for producing a permanent film for an electronic device.
[0083] Each component used in the photosensitive resin composition will be described in detail below. The polymer P is as described above. (Crosslinking agent) The photosensitive resin composition of the present embodiment includes a crosslinking agent. The crosslinking agent is not limited as long as it is a compound containing a functional group capable of reacting with the active hydrogen of the polymer P. Examples of such crosslinking agents include compounds having at least one functional group selected from a glycidyl group, an oxetanyl group, and a blocked isocyanate group. As the crosslinking agent, a compound having a glycidyl group or an oxetanyl group is more preferable, and a compound having a glycidyl group is even more preferable. By using such a crosslinking agent, a suitable crosslinked structure can be formed. In addition, as the crosslinking agent, one or more types selected from a compound having a blocked isocyanate group, an epoxy compound, and an oxetane compound can be used in combination.
[0084] Examples of compounds having a glycidyl group that can be used as a crosslinking agent include glycidyl ethers such as allyl glycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, glycerol polyglycidyl ether, sorbitol polyglycidyl ether, and glycidyl ether of bisphenol A (or F), glycidyl esters such as adipic acid diglycidyl ester and o-phthalic acid diglycidyl ester, 3,4-epoxycyclohexylmethyl (3,4-epoxycyclohexane) carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl ( ... -methylcyclohexane)carboxylate, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, dicyclopentanediene oxide, bis(2,3-epoxycyclopentyl)ether, alicyclic epoxies such as Celloxide 2021, Celloxide 2081, Celloxide 2083, Celloxide 2085, Celloxide 8000, and Epolead GT401 manufactured by Daicel Corporation, 2,2'-(((((1-(4-(2-(4-(oxiran-2-ylmethoxy)phenyl)propan-2-yl)phenyl)ethane-1,1-diyl)bis(4,1-phenylene))bis(oxy))bis(methylene))bis(oxirane) (for example, Techmore Aliphatic glycidyl ethers such as VG3101L (manufactured by Printec), Epolite 100MF (manufactured by Kyoeisha Chemical Industry Co., Ltd.), Epiol TMP (manufactured by NOF Corp.), and 1,4-cyclohexanedimethanol diglycidyl ether (manufactured by New Japan Chemical Co., Ltd., Showa Denko K.K., etc.), aromatic glycidyl ethers such as 3,3',5,5'-tetramethyl-4,4'-bis(glycidyloxy)-1,1'-biphenyl, and epoxy resins such as 1,1,3,3,5,5-hexamethyl-1,5-bis(3-(oxiran-2-yl methoxy)propyl)trisiloxane (e.g., DMS-E09 (manufactured by Gelest Co., Ltd.)) can be used.
[0085] Further, for example, bisphenol A type epoxy resins such as LX-01 (manufactured by Daiso Co., Ltd.), jER1001, jER1002, jER1003, jER1004, jER1007, jER1009, jER1010, jER828, and jER825 (trade names; manufactured by Mitsubishi Chemical Corporation), bisphenol F type epoxy resins such as jER807 (trade name; manufactured by Mitsubishi Chemical Corporation), phenol novolac type epoxy resins such as jER152 and jER154 (trade names; manufactured by Mitsubishi Chemical Corporation), EPPN201 and EPPN202 (trade names; manufactured by Nippon Kayaku Co., Ltd.), EOCN102, EOCN103S, EOCN104S, EOCN1020, 1025, and 1027 (trade names; manufactured by Nippon Kayaku Co., Ltd.), and the like. cresol novolak type epoxy resins such as Araldite CY179, CY184 (trade name; manufactured by Huntsman Advanced Materials), ERL-4206, 4221, 4234, 4299 (trade name; manufactured by Dow Chemical Company), Epiclon 200, 400 (trade name; manufactured by DIC Corporation), jER871, 872 (trade name; manufactured by Mitsubishi Chemical Corporation), and other cyclic aliphatic epoxy resins; poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propanediol ether (3:1) and other polyfunctional alicyclic epoxy resins; and EHPE-3150 (manufactured by Daicel Corporation) can also be used.
[0086] Examples of compounds having an oxetanyl group that can be used as a crosslinking agent include 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, bis[1-ethyl(3-oxetanyl)]methyl ether, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, 4,4'-bis(3-ethyl-3-oxetanylmethoxy)biphenyl, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, and diethylene glycol bis(3-ethyl-3-oxetanylmethyl). Examples of oxetane compounds include oxetane compounds such as ether, bis(3-ethyl-3-oxetanylmethyl)diphenoate, trimethylolpropane tris(3-ethyl-3-oxetanylmethyl)ether, pentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl)ether, poly[[3-[(3-ethyl-3-oxetanyl)methoxy]propyl]silasesquioxane] derivatives, oxetanyl silicate, phenol novolac-type oxetane, and 1,3-bis[(3-ethyloxetan-3-yl)methoxy]benzene.
[0087] The compound having a blocked isocyanate group used as a crosslinking agent is not limited, but for example, it is a compound in which the isocyanate group of a polyfunctional isocyanate is protected by a blocking agent.
[0088] The polyfunctional isocyanate is an organic compound having a plurality of isocyanate groups in one molecule. Examples of the polyfunctional isocyanate include 1,4-tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, lysine diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate), 1,3-bis(isocyanatomethyl)-cyclohexane, 4,4'- Examples of the isocyanate compound include dicyclohexylmethane diisocyanate, tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, xylylene diisocyanate, and the like; and derivatives of the above diisocyanate compounds, such as isocyanurate-modified polyfunctional isocyanate, biuret-modified polyfunctional isocyanate, and urethane-modified polyfunctional isocyanate.
[0089] Examples of the blocking agent include one or more selected from alcohol-based compounds, phenol-based compounds, active methylene-based compounds, mercaptan-based compounds, acid amide-based compounds, acid imide-based compounds, imidazole-based compounds, urea-based compounds, oxime-based compounds, amine-based compounds, imine-based compounds, bisulfites, pyridine-based compounds, and the like.
[0090] Specific examples of blocking agents include alcohol compounds such as methanol, ethanol, propanol, butanol, 2-ethylhexanol, methyl cellosolve, butyl cellosolve, methyl carbitol, benzyl alcohol, and cyclohexanol; phenol compounds such as phenol, cresol, ethylphenol, butylphenol, nonylphenol, dinonylphenol, styrenated phenol, and hydroxybenzoic acid ester; active methylene compounds such as dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; mercaptan compounds such as butyl mercaptan and dodecyl mercaptan; acetanilide, acetic acid amide, Examples of the compounds include acid amide compounds such as ε-caprolactam, δ-valerolactam, and γ-butyrolactam; acid imide compounds such as succinimide and maleimide; imidazole compounds such as imidazole and 2-methylimidazole; urea compounds such as urea, thiourea, and ethyleneurea; oxime compounds such as formaldoxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, and cyclohexanone oxime; amine compounds such as diphenylamine, aniline, and carbazole; imine compounds such as ethyleneimine and polyethyleneimine; bisulfites such as sodium bisulfite; and pyridine compounds such as 2-hydroxypyridine and 2-hydroxyquinoline.
[0091] Specific examples of compounds having a blocked isocyanate group used as such crosslinking agents include Burnock D-500 (blocked with tolylene diisocyanate), Burnock D-550 (blocked with 1,6-hexamethylene diisocyanate), and Burnock D-980K (blocked with 1,6-hexamethylene diisocyanate), all manufactured by Dainippon Ink and Chemicals, Inc.; Takenate B-830 (blocked with tolylene diisocyanate), Takenate B-815N (blocked with 4,4'-methylenebis(cyclohexylisocyanate)), Takenate B-842N (blocked with 1,3-bis(isocyanatomethyl)cyclohexane), and Takenate B-846N (blocked with 1,3-bis(isocyanatomethyl)cyclohexane), all manufactured by Mitsui Takeda Chemicals, Inc. Examples of the blocked polymer include Takenate B-874N (blocked with isophorone diisocyanate), Takenate B-882N (blocked with 1,6-hexamethylene diisocyanate), Takenate B-890 (blocked with xylylene diisocyanate); Takenate B-820NP (blocked with 1,3-bis(isocyanate methyl)cyclohexane), Takenate B-885N (blocked with 1,6-hexamethylene diisocyanate); and Asahi Kasei's Duranate MF-B60X (blocked with 1,6-hexamethylene diisocyanate) and Duranate MF-K60X (blocked with 1,6-hexamethylene diisocyanate).
[0092] (Photosensitizer) When the photosensitive resin composition is a positive type, a photoactive compound such as a diazoquinone compound can be used as the photosensitizer. For example, any one or more of the following compounds may be used:
[0093] [ka]
[0094] [ka]
[0095] [ka] (n2 is an integer between 1 and 5.)
[0096] [ka]
[0097] [ka]
[0098] [ka]
[0099] In each of the above compounds, Q is one of the structures shown below or a hydrogen atom, with the proviso that at least one of Q in each compound is one of the structures shown below. Among these, from the viewpoints of the transparency and dielectric constant of the photosensitive resin composition, o-naphthoquinone diazide sulfonic acid derivatives in which Q is (a) or (b) are preferred.
[0100] [ka]
[0101] In addition to the above-mentioned photoactive compound, the positive-type photosensitive resin composition may contain an acid generator that generates an acid by light or heat. By containing such an acid generator, the crosslinking reaction of the crosslinking agent can be promoted by irradiating the photosensitive resin composition with light or heating after exposure and development. In this case, the amount of the acid generator is preferably 3 parts by mass or less based on 100 parts by mass of the crosslinking agent. As the photoacid generator that generates an acid by exposure to light, those described below can be used. As a thermal acid generator that generates an acid by heat, an aromatic sulfonium salt such as SI-45L, SI-60L, SI-80L, SI-100L, SI-110L, or SI-150L (manufactured by Sanshin Chemical Industry Co., Ltd.) can be used. The content of the thermal acid generator is preferably, for example, 0.1% by mass or more and 5% by mass or less when the total solid content of the photosensitive resin composition is taken as 100% by mass. In this embodiment, the total solid content of the photosensitive resin composition refers to the components excluding the solvent.
[0102] In addition, when the photosensitive resin composition is a negative type, a photoacid generator can be used as the photosensitizer. The photoacid generator may be any one that absorbs the energy of light to generate a Bronsted acid or a Lewis acid, and examples of the photoacid generator include sulfonium salts such as triphenylsulfonium trifluoromethanesulfonate and tris(4-t-butylphenyl)sulfonium-trifluoromethanesulfonate; diazonium salts such as p-nitrophenyldiazonium hexafluorophosphate; ammonium salts; phosphonium salts; diphenyliodonium trifluoromethanesulfonate and (tricumyl)iodonium-tetrakis(pentafluorophenyl)borate; Examples of the photoacid generator include iodonium salts such as quinone diazides and diazomethanes such as bis(phenylsulfonyl)diazomethane, sulfonic acid esters such as 1-phenyl-1-(4-methylphenyl)sulfonyloxy-1-benzoylmethane and N-hydroxynaphthalimide-trifluoromethanesulfonate, disulfones such as diphenyl disulfone, and triazines such as tris(2,4,6-trichloromethyl)-s-triazine and 2-(3,4-methylenedioxyphenyl)-4,6-bis(trichloromethyl)-s-triazine. These photoacid generators can be used alone or in combination.
[0103] In addition, when the photosensitive resin composition is a negative type, the composition may contain a second crosslinking agent that crosslinks the copolymer by the action of an acid. This second crosslinking agent crosslinks the copolymer by using the acid generated by the photoacid generator as a catalyst, and is different from the compound used for the crosslinking agent. For example, melamine-based crosslinking agents and urea-based crosslinking agents can be used. Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, and hexabutoxybutylmelamine, with hexamethoxymethylmelamine being preferred. Examples of the urea-based crosslinking agent include methylated urea resin, bismethoxymethylurea, bisethoxymethylurea, bispropoxymethylurea, bisbutoxymethylurea, and the like, and among these, methylated urea resin is preferred. Commercially available methylated urea resins include, for example, MX-270, MX-280, and MX-290 (manufactured by Sanwa Chemical Co., Ltd.).
[0104] The proportion of the second crosslinking agent in the negative photosensitive resin composition is preferably 5% by mass or more and 40% by mass or less, and from the viewpoint of resolution, more preferably 5% by mass or more and 30% by mass or less, and even more preferably 10 to 25% by mass, when the total solid content of the resin composition is 100% by mass.
[0105] In the above photosensitive resin composition, when the photosensitive resin composition is a positive type, the ratio of each component is, for example, as follows. When the total solid content of the photosensitive resin composition is taken as 100 mass%, the photosensitive resin composition preferably contains the above-mentioned copolymer in an amount of, for example, 30 mass% or more and 70 mass% or less, and more preferably 40 mass% or more and 60 mass% or less. When the total solid content of the photosensitive resin composition is taken as 100 mass%, the crosslinking agent is preferably contained in an amount of, for example, 15 mass% or more and 50 mass% or less, and more preferably 20 mass% or more and 50 mass% or less. Furthermore, when the total solid content of the photosensitive resin composition is taken as 100 mass%, the photoactive compound serving as a photosensitizer is preferably contained in an amount of, for example, 5 mass% or more and 40 mass% or less, and more preferably 10 mass% or more and 30 mass% or less.
[0106] When the photosensitive resin composition is a negative type, the ratio of each component is, for example, as follows: When the total solid content of the photosensitive resin composition is taken as 100 mass%, the photosensitive resin composition preferably contains the above-mentioned copolymer in an amount of, for example, 30 mass% or more and 70 mass% or less, and more preferably 40 mass% or more and 60 mass% or less. In addition, when the total solid content of the photosensitive resin composition is taken as 100 mass%, the crosslinking agent (excluding the second crosslinking agent) is preferably contained in an amount of, for example, 15 mass% or more and 50 mass% or less, and more preferably 20 mass% or more and 50 mass% or less. Furthermore, when the total solid content of the photosensitive resin composition is taken as 100 mass%, the amount of the photoacid generator is, for example, 0.1 mass% or more and 40 mass% or less, and from the viewpoint of forming a pattern film with high resolution, it is more preferably 1 mass% or more and 30 mass% or less.
[0107] The photosensitive resin composition may further contain additives such as a solvent, an antioxidant, a surfactant, an adhesion aid, a dissolution promoter, a filler, a sensitizer, and polyphenols.
[0108] (Resin film) The resin film according to this embodiment is made of a cured product of the above-mentioned photosensitive resin composition. This resin film has excellent heat resistance and is therefore used as a resist or permanent film in electronic devices.
[0109] When the resin film of the present embodiment is used as a resist, the resist is produced by applying the photosensitive resin composition of the present embodiment by a method such as spin coating, roll coating, flow coating, dip coating, spray coating, or doctor coating to obtain a coating film, and then removing the solvent.
[0110] When the resin film of the present embodiment is used as a permanent film, the coating film of the photosensitive resin composition obtained as described above is exposed to light and developed, patterned into a desired shape, and then cured by heat treatment, etc. The permanent film can be used, for example, as a protective film or an interlayer film for electronic devices.
[0111] The electronic device according to the present embodiment includes the resin film.
[0112] The electronic device of the present embodiment includes the above-described resin film. For example, when the electronic device is a semiconductor chip, a passivation film and an insulating layer constituting the semiconductor chip are formed from a cured product of the photosensitive resin composition of this embodiment.
[0113] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES
[0114] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0115] (Synthesis Example 1: Synthesis of Precursor Polymer A) In a suitable reaction vessel, 5-nonafluorobutylbicyclo[2.2.1]hept-2-ene (NBC4F9, 22.9 g, 72.8 mmol), maleic anhydride (MAN, 7.1 g, 72.8 mmol), 2,2'-azobis(2-methylpropionate)dimethyl (Wako Pure Chemical Industries, trade name: V-601, 3.4 g, 14.6 mmol) as an initiator, and 9.5 g of methyl ethyl ketone (MEK) were added and dissolved by stirring. Then, the dissolved oxygen in the system was removed by nitrogen bubbling, and the mixture was heated and reacted at an internal temperature of 60°C for 16 hours. The reaction mixture was then cooled to room temperature, and 32.1 g of MEK was added to dilute the mixture. The diluted solution was poured into a large amount of methanol to precipitate the polymer. The polymer was then filtered, washed with methanol, and vacuum dried at 120°C for 16 hours. The polymer yield was 25.0 g, and the yield was 83%. The polymer had a weight average molecular weight Mw of 2,400 and a dispersity (weight average molecular weight Mw / number average molecular weight Mn) of 1.69.
[0116] (Synthesis Example 2: Synthesis of Precursor Polymer B) In a suitable reaction vessel, NBC4F9 (22.9 g, 72.8 mmol), MAN (7.1 g, 72.8 mmol), V-601 (1.7 g, 7.3 mmol) and MEK 11.2 g were added and dissolved by stirring. Then, the dissolved oxygen in the system was removed by nitrogen bubbling, and the mixture was heated and reacted at an internal temperature of 60°C for 5 hours. Then, the internal temperature was raised to 80°C and the mixture was reacted for another 3 hours. The reaction mixture was cooled to room temperature and poured into a large amount of methanol to precipitate the polymer. The polymer was then filtered, washed with methanol, and vacuum dried at 120°C for 16 hours. The yield of the polymer was 14.9 g, and the yield was 50%. The polymer had an Mw of 4,000 and an Mw / Mn of 1.50.
[0117] (Synthesis Example 3: Synthesis of Precursor Polymer C) Maleic anhydride (Nippon Shokubai Co., Ltd., 24.3 g, 247.8 mmol), bicyclo[2.2.1]hept-5-ene-2-carboxylate-3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl (NBCOOC2H4C6F13, 120.0 g, 247.8 mmol) and dimethyl 2,2'-azobis(2-methylpropionate) (V-601, Fujifilm Wako Pure Chemical Industries, Ltd., 7.61 g, 30.6 mmol) were weighed and dissolved in methyl ethyl ketone (MEK, 28.5 g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. After removing oxygen by passing nitrogen through the solution for 10 minutes, the temperature was raised to 60°C while stirring and maintained for 2 hours. The temperature was then raised to 80°C and maintained for 3 hours, after which V-601 (3.81 g, 15.3 mmol) was added and reacted for another 3 hours. The reaction mixture was diluted with MEK and then dropped into a large amount of methanol to precipitate a polymer. After filtration using a Nutsche funnel, the solid was washed with methanol and vacuum dried. The weight average molecular weight (Mw) of the obtained polymer was 5,400 and the dispersity (Mw / Mn) was 1.72.
[0118] (Synthesis Example 4: Synthesis of Precursor Polymer D) Maleic anhydride (4.76 g, 48.5 mmol), 5-tridecafluorohexyl-2-norbornene (NBC6F13, 20.0 g, 48.5 mmol) and V-601 (1.5 g, 6.0 mmol) were weighed and dissolved in MEK (4.7 g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. Nitrogen was passed through the solution for 10 minutes to remove oxygen, and the solution was then heated to 60°C with stirring and held for 2 hours. The solution was then heated to 80°C and held for 3 hours, after which V-601 (0.74 g, 3.0 mmol) was added and reacted for another 3 hours. The reaction mixture was diluted with MEK and then dropped into a large amount of methanol to precipitate a polymer. After filtration using a Nutsche funnel, the solid was washed with methanol and vacuum dried. The weight average molecular weight (Mw) of the obtained polymer was 3,700 and the dispersity (Mw / Mn) was 1.64.
[0119] Table 1 shows the amounts of the components used in Synthesis Examples 1 to 4, as well as the weight average molecular weights and dispersities of the obtained precursor polymers.
[0120] [Table 1]
[0121] (Synthesis Example 5: Synthesis of fluorine-containing polymer A-1) 15.0 g of the precursor polymer A synthesized in Synthesis Example 1 was dissolved in 27.9 g of MEK. 3.0 g of 2-hydroxyethyl methacrylate (HEMA) and 1.5 g of triethylamine (TEA) were further added, and the mixture was heated to 70°C and reacted for 6 hours. Then, 1.6 g of glycidyl methacrylate (GMA) was added, and the mixture was reacted for another 4 hours. The reaction mixture was cooled to room temperature and neutralized with formic acid. The solution was poured into a large amount of pure water to precipitate the polymer. The obtained polymer was filtered and washed with pure water, and then dissolved in propylene glycol monomethyl ether acetate (PGMEA). The remaining water was removed and concentrated under reduced pressure to obtain a polymer solution with a solid content of about 35%. The weight average molecular weight (Mw) of the polymer thus obtained was 2,100, the molecular weight distribution was 1.55, the double bond equivalent was 1,700 g / mol, and the fluorine content in the polymer solids was 30 wt%.
[0122] (Synthesis Example 6: Synthesis of fluorine-containing polymer B-1) 5.0 g of the precursor polymer B synthesized in Synthesis Example 2 was dissolved in 27.9 g of MEK. 1.0 g of 2-hydroxyethyl methacrylate (HEMA) and 0.75 g of triethylamine (TEA) were further added, and the mixture was heated to 70°C and reacted for 6 hours. Next, 0.5 g of glycidyl methacrylate (GMA) and 1.0 g of 3-perfluorobutyl-1,2-epoxypropane (PFBEp) were added, and the mixture was further reacted at 70°C for 4 hours. The reaction mixture was cooled to room temperature and neutralized with formic acid. The solution was poured into a large amount of pure water to precipitate the polymer. The obtained polymer was filtered and washed with pure water, and then dissolved in PGMEA. The remaining water was removed and concentrated under reduced pressure to obtain a polymer solution with a solid content of about 35%. The weight average molecular weight (Mw) of the polymer thus obtained was 4,000, the molecular weight distribution was 1.50, the double bond equivalent was 1,100 g / mol, and the fluorine content in the polymer solids was 33 wt%.
[0123] (Synthesis Example 7: Synthesis of fluorine-containing polymer C-1) The precursor polymer C (10.0 g) synthesized in Synthesis Example 3 was weighed and dissolved in MEK (10 g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. 4-Hydroxybutyl acrylate (4HBA, manufactured by Mitsubishi Chemical Corporation, 2.48 g, 17.2 mmol) and triethylamine (2.0 g) were further added and heated at 70°C for 6 hours. After acid treatment with formic acid, the reaction solution was dropped into a large amount of pure water to precipitate the polymer. PGMEA was added to the filtered solid and concentrated to obtain a PGMEA solution of the polymer. Mw was 4,900, Mw / Mn was 1.81, and double bond equivalent was 1,600 g / mol. The fluorine content in the polymer was 34 wt%.
[0124] (Synthesis Example 8: Synthesis of fluorine-containing polymer D-1) The precursor polymer D (10.0 g) synthesized in Synthesis Example 4 was weighed and dissolved in MEK (10 g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. 4HBA (2.83 g, 17.2 mmol) and triethylamine (2.0 g) were further added and heated at 70°C for 6 hours. After acid treatment with formic acid, the reaction solution was dropped into a large amount of pure water to precipitate the polymer. PGMEA was added to the filtered solid and concentrated to obtain a PGMEA solution of the polymer. Mw was 3,900, Mw / Mn was 1.60, and double bond equivalent was 1,400 g / mol. The fluorine content in the polymer was 39 wt%.
[0125] (Synthesis Example 9: Synthesis of Polymer 1) 2-Norbornene (75wt% toluene solution, Maruzen Petrochemicals, 125.5g, 1.00mol) and dimethyl 2,2'-azobis(2-methylpropionate) (V-601, Wako Pure Chemical Industries, 9.2g, 40mmol) were weighed and dissolved in methyl ethyl ketone (MEK, 196.1g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. Nitrogen was passed through the solution for 10 minutes to remove oxygen, and the solution was heated to 80°C while stirring. While maintaining the solution at 80°C, a solution of maleic anhydride (Nippon Shokubai, 98.1g, 1.00mol) previously prepared in 119.9g of MEK was added dropwise over 1.5 hours, and the reaction was continued at that temperature for another 8 hours. The reaction mixture was added dropwise to a large amount of methanol to precipitate a polymer. After filtering using a Nutsche filter, the solid was further washed with methanol and dried in vacuum at 70°C. The weight average molecular weight (Mw) of the obtained polymer was 6,900 and the dispersity (Mw / Mn) was 1.76.
[0126] The above-mentioned precursor polymer (50.0 g) was weighed and dissolved in MEK (90 g) in a suitable size reaction vessel equipped with a stirrer and a cooling tube. 2-Hydroxyethyl methacrylate (HEMA, Nippon Shokubai Co., Ltd., 21.2 g, 163 mmol) and triethylamine (5.0 g) were further added and heated at 70 ° C for 6 hours. Glycidyl methacrylate (GMA, 11.1 g, 78 mmol) was added to this reaction liquid and further stirred at 70 ° C for 4 hours. After acid treatment by adding formic acid to the reaction liquid, it was dropped into a large amount of pure water to precipitate the polymer. The filtered solid was dried in a vacuum dryer at 40 ° C for 16 hours to obtain a polymer. Mw was 7,800 and Mw / Mn was 1.70. The double bond equivalent was 540 g / mol.
[0127] (Weight average molecular weight / molecular weight distribution) In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) are polystyrene equivalent values obtained from a calibration curve of standard polystyrene (PS) obtained by GPC measurement. The measurement conditions are as follows. Tosoh gel permeation chromatography device HLC-8320GPC Column: Tosoh TSK-GEL Supermultipore HZ-M Detector: RI detector for liquid chromatography Measurement temperature: 40℃ Solvent: THF Sample concentration: 2.0 mg / ml
[0128] (double bond equivalent) The double bond equivalent of the fluorine-containing polymers A-1 to D-1 was measured by the following method. First, about 50 mg of the polymer from which the solvent had been removed by drying under reduced pressure and about 5 mg of dimethyl terephthalate as an internal standard substance were weighed and dissolved in DMSO-d6. This solution was subjected to 1H-NMR measurement using a nuclear magnetic resonance spectrometer JNM-AL300 (manufactured by JEOL). The polymer weight per mole of double bond (g / mol, double bond equivalent) was calculated from the integral ratio of the signal (5-7 ppm) derived from the (meth)acrylic group in the obtained spectrum chart to the signal (4H, 8.1 ppm) of the phenyl group of the internal standard substance.
[0129] (Measurement of fluorine content) The fluorine content of the fluorine-containing polymers A-1 to D-1 was measured by the following method. First, about 10 mg of the polymer, which had been dried under reduced pressure to remove the solvent, was completely combusted in a sealed flask purged with oxygen. The generated gas was collected in an alkaline hydrogen peroxide absorption solution that had been added in advance, and the solution was adjusted to a constant volume of 50 mL to obtain a test solution. The test solution and the standard solution were introduced into an ion chromatograph (ICS-3000 type chromatograph manufactured by Dionex Corporation), and the concentration of fluoride ions was determined by the calibration curve method, and the amount of fluorine contained in the sample was calculated.
[0130] (Refractive index measurement) The refractive index of fluorine-containing polymers A-1 to D-1 was measured by the following method. The polymer was dissolved in PGMEA at a concentration of 35% by weight. The obtained polymer solution was spin-coated on a 3-inch silicon wafer and heat-treated at 100°C for 120 seconds to obtain a thin film of 1.0 to 1.5 μm. The refractive index at a wavelength of 632.8 nm was measured using a prism coupler (METRICON MODEL2010M).
[0131] (Alkaline dissolution rate) The alkaline dissolution rate of the fluorine-containing polymers A-1 to D-1 was measured as follows. The polymer was dissolved in PGMEA to prepare a solution with a solid concentration of 35%. This polymer solution was applied by spin coating onto a silicon wafer, which was soft-baked at 100°C for 120 seconds to form a polymer film with a thickness H of about 2.0 μm. The silicon wafer on which this polymer film was formed was immersed in a 2.38% aqueous solution of tetramethylammonium hydroxide at 23°C, and the time T until the polymer film was visually erased was measured. The alkaline dissolution rate was calculated from H and T using the following formula. (Alkaline dissolution rate) [Å / sec] = (film thickness H) / (time until polymer film is erased T)
[0132] Table 2 shows the amounts of the components used in Synthesis Examples 5 to 8, as well as the weight average molecular weight distribution, double bond equivalent, fluorine content, refractive index, and alkali dissolution rate of the resulting fluorine-containing polymers.
[0133] [Table 2]
[0134] (Preparation of Photosensitive Resin Composition) For each Example and Comparative Example, the polymers prepared in Synthesis Examples 5 to 9, photosensitizers, crosslinking agents, adhesion improvers, and surfactants were dissolved in PGMEA and cyclohexanone in the amounts shown in Table 3, and then stirred. After stirring, the mixture was filtered through a 0.2 μm filter to prepare negative photosensitive resin compositions.
[0135] The following components were used as shown in Table 3. (Fluorine-containing polymer) Polymer A-1: Fluorine-containing polymer A-1 prepared in Synthesis Example 5 Polymer B-1: Fluorine-containing polymer B-1 prepared in Synthesis Example 6 Polymer C-1: Fluorine-containing polymer C-1 prepared in Synthesis Example 7 Polymer D-1: Fluorine-containing polymer D-1 prepared in Synthesis Example 8 (Other polymers) Polymer 1: Polymer 1 prepared in Synthesis Example 9 (Crosslinking agent) Crosslinking agent 1: An acrylic crosslinking agent represented by the following formula (12) (DPHA manufactured by Daicel-Cytec Co., Ltd.).
[0136] [ka]
[0137] (Photosensitizer) Photosensitizer 1: A photoradical polymerization initiator represented by the following formula (11) (Irgacure OXE02 manufactured by BASF) was used.
[0138] [ka]
[0139] (Adhesion aid) Adhesion aid 1: 3-glycidoxypropyltrimethoxysilane (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0140] (Surfactant) Surfactant 1: Megafac F-556 (DIC Corporation)
[0141] (solvent) Solvent 1: Propylene glycol monomethyl ether acetate (PGMEA) Solvent 2: Cyclohexanone
[0142] The negative photosensitive resin compositions obtained as described above were evaluated for the following items.
[0143] (Sensitivity evaluation) The negative photosensitive resin compositions thus prepared were each applied onto a 3-inch silicon wafer using a spin coater. After application, the wafer was prebaked on a hot plate at 100° C. for 2 minutes to obtain a coating film (thin film A) having a thickness of about 3.0 μm. This thin film was irradiated with 100 mJ / cm2 at 100 mJ / cm3 using a Canon g+h+i line mask aligner (PLA-501F) through a photomask with a transmittance of 1 to 100%. 2 The sample was exposed to g+h+i rays at an exposure dose of 100 nm. After exposure, the unexposed areas were dissolved and removed by developing at 23°C for 60 seconds using 2.38% tetramethylammonium hydroxide as a developer, and 1 to 100 mJ / cm 2 A thin film (thin film B) was obtained by exposing the thin film to each of the above exposure doses.
[0144] From the film thicknesses of Thin Film A and Thin Film B obtained by the above method, the remaining film rate was calculated according to the following formula. Residual film rate after development (%) = {(film thickness of thin film B at each exposure dose (μm)) / (film thickness of thin film A (μm))} × 100 The minimum exposure dose at which the post-development residual film rate obtained by the above formula was 95% or more was taken as the sensitivity of the resist.
[0145] (Measurement of dielectric constant) After applying the photosensitive resin composition to a low-resistance silicon wafer (Ω<), the solvent was removed by heat treatment at 100°C for 120 seconds. Then, the wafer was irradiated with 100 mJ / cm using a Canon g+h+i-line mask aligner (PLA-501F). 2 The entire surface was exposed to g+h+i rays at an exposure dose of 1000 nm. The obtained film was heat-treated in an oven at 230° C. in the atmosphere for 60 minutes to cure the photosensitive resin composition. In this manner, a cured film was obtained for each of the Examples and Comparative Examples. A gold electrode was formed on this thin film, and the dielectric constant was calculated from the obtained capacitance using a Hewlett Packard LCR meter (4282A) at room temperature and 100 kHz.
[0146] (Evaluation of chemical resistance) After applying the photosensitive resin composition to a 3-inch silicon wafer, the solvent was removed by heat treatment at 100°C for 120 seconds. Then, the wafer was irradiated with 100 mJ / cm 2 using a Canon g+h+i line mask aligner (PLA-501F). 2The entire surface was exposed to g+h+i rays at an exposure dose of 1000 nm. The obtained film was heat-treated in an oven in the atmosphere at 230°C for 60 minutes to cure the photosensitive resin composition. In this manner, a cured film was obtained for each of the Examples and Comparative Examples. The obtained silicon wafer with the cured film was immersed in TOK106 (manufactured by Tokyo Ohka Kogyo Co., Ltd.) at room temperature for 5 minutes, and then rinsed with pure water for 30 seconds. At this time, the film thickness change rate defined by the following calculation formula was calculated and used as an index of chemical resistance. A smaller film thickness change rate indicates better chemical resistance. Film thickness change rate (%) = [{(film thickness after immersion in chemical solution) - (film thickness before immersion in chemical solution)} / (film thickness before immersion in chemical solution)] × 100
[0147] (Evaluation of light transmittance) The photosensitive resin composition was applied to a Corning 1737 glass substrate measuring 100 mm in length and 100 mm in width, and then the solvent was removed by heat treatment at 100°C for 120 seconds. Then, the substrate was subjected to a 100 mJ / cm 2 irradiation with a Canon g+h+i line mask aligner (PLA-501F). 2 The entire surface was exposed to g+h+i rays at an exposure dose of 1000 g / cm. The obtained film was heat-treated in an oven at 230°C in the atmosphere for 60 minutes to cure the photosensitive resin composition. In this manner, a cured film was obtained for each of the Examples and Comparative Examples. The transmittance (%) of this cured film at a wavelength of 400 nm was measured using an ultraviolet-visible light spectrophotometer, and the value converted to a film thickness of 3 μm was taken as the transmittance.
[0148] (Evaluation of heat resistance) For each example, the weight loss rate of the cured film was evaluated using the obtained photosensitive resin composition as follows. First, the photosensitive resin composition was applied to a 3-inch wafer, and then the solvent was removed by heat treatment at 100°C for 120 seconds. Then, the composition was irradiated with 100 mJ / cm using a Canon g+h+i line mask aligner (PLA-501F). 2 The entire surface was exposed to g+h+i rays at an exposure dose of 1000 g / cm. The obtained film was heat-treated in an oven at 230° C. in air for 60 minutes to cure the photosensitive resin composition. In this way, a cured film was obtained for each of the examples and comparative examples. Next, the weight loss rate of the above sample was measured. The measurement was performed using a thermogravimetric / differential thermal analyzer (TG / DTA) for a sample obtained by weighing 5 mg of the cured film, with a starting temperature of 30° C., a heating rate of 10° C. / min, and N 2 The temperature was raised to 250° C. under the condition of a flow rate of 200 mL / min, and the mixture was maintained at 250° C. for 60 minutes. The rate of change in weight from the weight at 250° C. until 60 minutes had elapsed was defined as the weight loss rate. The evaluation results for the above items are shown in Table 3.
[0149] [Table 3]
[0150] The cured products of the photosensitive resin compositions of the Examples had low dielectric constants and excellent heat resistance and chemical resistance.
[0151] This application claims priority based on Japanese Patent Application No. 2019-175111, filed on September 26, 2019, the disclosure of which is incorporated herein in its entirety.
Claims
1. A polymer comprising structural units represented by the following formulas (1) and (2a): 【Chemistry 1】 (In formula (1), R 1 , R 2 , R 3 and R 4 at least one of the groups is a perfluoroalkyl group having 1 to 30 carbon atoms, the remainder are hydrogen atoms, and n is 0, 1, or 2; In formula (2a), R 5 is an organic group having 1 to 30 carbon atoms and having a (meth)acryloyl group.
2. The polymer of claim 1, further comprising at least one of the structural units represented by formulas (B2) to (B6). 【Chemistry 2】 (In formula (B2), R 6 and R 7 are each independently an organic group having 1 to 30 carbon atoms. 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 (In formula (B6), R 8 is an organic group having 1 to 30 carbon atoms.
3. The polymer according to claim 1 or 2, having a weight average molecular weight of 1,500 or more and 30,000 or less.
4. A polymer comprising structural units represented by the following formulas (1) and (2a): A cross-linking agent; A photosensitive resin composition comprising: 【Chemistry 7】 (In formula (1), R 1 , R 2 , R 3 and R 4 at least one of the groups is a perfluoroalkyl group having 1 to 30 carbon atoms, the remainder are hydrogen atoms, and n is 0, 1, or 2; In formula (2a), R 5 is an organic group having 1 to 30 carbon atoms and having a (meth)acryloyl group.
5. The photosensitive resin composition according to claim 4, wherein the polymer further comprises at least one of the structural units represented by formulae (B2) to (B6). 【Chemistry 8】 (In formula (B2), R 6 and R 7 are each independently an organic group having 1 to 30 carbon atoms. 【Chemistry 9】 【Chemistry 10】 【Chemistry 11】 【Chemistry 12】 【change】 (In formula (B6), R 8 is an organic group having 1 to 30 carbon atoms.
6. The photosensitive resin composition according to claim 4 or 5, wherein the polymer has a weight average molecular weight of 1,500 or more and 30,000 or less.
7. A resin film comprising a cured film of the photosensitive resin composition according to any one of claims 4 to 6.
8. An electronic device comprising the resin film according to claim 7.
Citation Information
Patent Citations
Radiation-sensitive resin composition and method for forming resist pattern
JP2015184458A
Multi-cell lithium-ion battery
JP2015520935A
Polymers derived from norbornadiene and maleic anhydride and their uses
JP2019503415A
Photosensitive coloring resin composition, colored pattern, black matrix, color filter, liquid crystal display device, solid-state imaging element, and method for producing color filter
WO2016194619A1